The benefits and implementation of performance transparency: the why and how of letting your customers 'see through' your business - Merlo,OGL; Eisingerich,A; Auh,S; Levstek,J (Business Horizons, 2018)
While some organizations swear by the benefits of transparency and are eager to know how to implement it, many managers are still reluctant or even afraid to use it. Our research reveals that only a few innovative companies have taken steps to leverage a potentially useful form of transparency: the provision of accessible and objective information to customers (e.g., by sharing unbiased benchmark data, publishing unfiltered customer comments, or providing candid product reviews that may praise but also criticize the company’s products). Our study also shows that that many companies remain wary and view greater calls for transparency as a challenge to be managed rather than an opportunity to be traded upon. This is partly due to limited research into the performance benefits of giving customers access to objective information, and lack of practical guidelines on how to actually implement it. The current study addresses these shortcomings: first, by investigating whether performance transparency leads to customer outcomes that can be profitable for an organization; and second, by analyzing the characteristics of successful transparency initiatives in a wide range of industries. The research shows that customers exhibit more trust and are willing to pay a premium to deal with transparent businesses. Also, it uncovers seven effective approaches to implementing transparency. The key contributions of the study are therefore the provision of convincing empirical evidence about the benefits of performance transparency and ways in which management may implement it successfully.